Establishing the impacts of freshwater aquaculture in tropical Asia: the potential role of palaeolimnology. Issue 2 (December 2015) - Legaspi, Kenoses; Lau, A. Y. Annie; Jordan, Phil; Mackay, Anson; Mcgowan, Suzanne; Mcglynn, Gayle; Baldia, Susana; Papa, Rey Donne; Taylor, David
Abstract : Freshwater aquaculture is an important source of protein worldwide. Over‐exploitation of fisheries can, however, add severely to pressures on ecosystem functioning and services. In Southeast Asia, aquaculture in freshwater lakes contributes significantly to the economy and to reductions in poverty and nutritional insecurity. However, overstocking and excessive feeding of fish can lead to a degradation of affected water bodies, manifest as eutrophication, toxic algal blooms, losses of biodiversity and amenity, anoxia and, in extreme cases, collapse of fisheries. Projected increased warming and storminess associated with global climate change are likely to magnify existing problems. Matching levels of aquaculture production with ecological carrying capacity is therefore likely to become increasingly challenging, requiring levels of data and understanding that are rarely available, a problem that is impossible to rectify in the short term using standard limnological approaches. This paper reviews the development of freshwater aquaculture in the Philippines, associated environmental impacts, and relevant environmental regulations and regulatory bodies. The potential role of palaeolimnology, a science that is relatively under‐utilised in the tropics generally and in tropical Asia in particular, in complementing extant datasets, including monitoring records, is highlighted through reference to a preliminary study at Lake Mohicap. Lake Mohicap currently supports aquaculture and is one of a cluster of seven volcanic crater lakes on Luzon, the largest of the archipelago of islands forming the Philippines.